Multilevel determinants of child development in socially vulnerable Brazilian children: a longitudinal study - da Silva, Aline Pereira; Oliveira Silva, George; de Souza, Marta Rovery (Frontiers in Pediatrics, 2026)
Child development consists of a process that involves multiple factors interrelated to the acquisition of children's skills in different areas, such as language, motor, cognitive, emotional, and social. Although extensively explored in literature, there is a gap in how vulnerabilities faced by families can influence this outcome. Thus, this study aims to identify social, maternal, obstetric and familiar determinants of child development in vulnerable children. This is a longitudinal study, conducted in three evaluations between August 2018 and January 2022, with families from Central Brazil participating in the research Impact Evaluation of the Happy Child Program. Generalized Estimating Equations models were used to identify the determinants of child development, evaluated in this study by the Ages and Stages Questionnaire 3rd edition, comparing with sociodemographic, social support, obstetric, children's birth and growth, and family situation variables. Of the 320 families that participated in the study in the state of Goiás, 284 met the inclusion criteria. In general, at the 3 assessment times, the children presented good child development scores in all domains. Positive determinants of child development included growth monitoring and non-violent discipline, while negative determinants were maternal age between 30 and 39 years old and psychological aggression. The findings of the present study highlight critical areas for targeted interventions in child development, offering valuable insights into research and policy formulation for children living in vulnerability situations.